Prioritization of options for potato research for development: Results from a global expert survey. - Kleinwechter, U.; Hareau, Guy; Suarez, V. (CGIAR Research Program on Roots, Tubers and Bananas, 2014)
The results from the expert survey presented in this report provide an insight into the perceptions of the potato community of practice about the priorities and needs for potato research and offer evidence about the relative importance of individual research options and constraints.